2008
DOI: 10.1176/jnp.2008.20.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Nondysphoric Depression Following Stroke

Abstract: Right hemisphere damage may influence the presentation of depressive disorders ensuing after stroke by disrupting emotion processing mechanisms. Three-hundred and one consecutive admissions for acute stroke were examined and subjects meeting previously validated criteria for nondysphoric depression (i.e., depressive ideation without endorsement of sad emotions) were compared to dysphoric depression, and to nondepressed patients. Compared to dysphoric depression, nondysphoric depression showed more frequent rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Consistent with expectations, the non-depressed group was less functionally impaired than both depression groups (NDD and DD)[1][2][4][8][25]. Similar results have been reported among older nursing home dwellers [27], but no previous study reported social functional adaptation in older nursing home patients with NDD.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Consistent with expectations, the non-depressed group was less functionally impaired than both depression groups (NDD and DD)[1][2][4][8][25]. Similar results have been reported among older nursing home dwellers [27], but no previous study reported social functional adaptation in older nursing home patients with NDD.…”
Section: Discussionsupporting
confidence: 80%
“…Earlier studies have described NDD as subthreshold or subsyndromal depression (by definition not meeting DSM-V criteria)[1][4][7][8]. As expected (based on inclusion criteria) lower HAM-D scores were found among participants with NDD compared to DD [2][46][48][58].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations